Odpowiedzi

2010-03-08T19:45:04+01:00
C)6/4x-12=18/*4
6x-48=72
6x=120
x=20
d)x/6-1/6=1/*6
x-1=6
x=7
e)-4x+2=x/3/*3
-12x+6=x
-13x=-6
x=13/6
x=2 i 1/6
F)6/5-2/5x=-2/*5
6-2x=-10
6=-8x
x=-6/8
x=-3/4
g)6/4-9/4x=-6/*4
6-9x=-24
-9x=-30x
x=30/9
x=3 i 1/3
H)1/5x-3/5=9-x/*5
x-3=45-5x
-4x=48
x=-12
I)0.6+x=x+1:2/*20
12+20x=10x+10
10x=-2
x=-2/1z
x=-1/5
2010-03-08T20:07:31+01:00
C) e)-2(2x -1)=x/3 g)3/4(2-3X)=-6
6(1/4x-2)=18 -4x+2=x/3 6/4-9/4X=-6
6/4x-12=18 -4x-x/3=-2 /*3 -9/4x=-6-6/4
6/4x=18+12 -12x-x=-6 -9/4x=-30/4 /: (-9/4)
6/4x=30 / :6/4 -13x=-6 /: (-13) x=3/10
x=30*4/6 x=6/13
x=30

d) f)2/5(3-x)=-2 h)1/5(x-3)=9-x
x/6-1/6=1 6/5-2/5x=-2 1/5x-3/5=9-x
(x-1):6=1 /6 -2/5x=-2-6/5 1/5x+x=9+3/5
x-1=1 -2/5x=-16/5 /: (-2/5) 6/5x=48/5 /:6/5
x=1+1 x=8 x=64/5
x=2

i)
0,6+x=x+1:2 /*2
1,2+2x=x+1
2x-x=1-1,2
x=-0,2